EVALUASI SISTEM PENGENDALIAN INTERNAL BAHAN BAKU PRODUKSI PADA UD. XYZ DI SIDOARJO - Darno Darno; Anita Anita; Jaya Adi Gama Tengtarto; Kuswana Rama; Camelia Dewi R (Jurnal Logistik Indonesia, 2021)
The era of globalization, the industrial world is increasingly developing, there are many companies engaged in the industry that manage various kinds of products, there will be more competitive competition. The development of the company is increasing rapidly, with the level of use and need for raw materials that are relatively large and increasing consumer demand. Raw material inventory control system for its role is needed in companies with existing theories. The author intends to analyze "Evaluation Of The Internal Control System For Raw Material For The Smoothness Of The Production Prosess (Case Study at UD. XYZ di Sidoarjo)". The purpose of this study is to find out how the internal control system for raw material inventory can be used to facilitate all production processes or processing of raw materials at UD. Light Plastic Sidoarjo. The data analysis technique used and carried out is a qualitative descriptive technique, which is to compare the collected data on a theoretical basis as a reference material that provides several suggestions for problem solvers in writing. Based on the results of research that can be done that the processing process in the company includes: the stage of purchasing raw materials, the stage of storing raw materials, the processing stage, the distribution stage. The research was conducted using a case study approach with qualitative methods. Data collection methods are carried out, namely interviews, observation and documentation. Based on the analysis, it is concluded that the internal control system for raw material inventory can expedite the processing or production process in the company which is said to be good, but there are still some weaknesses, namely concurrency in work, lack of monitoring of the production process or processing time and the entry and exit of goods in the company.